Collaboration of multi-stakeholder in integrated aid model for creative MSMEs in the tourism sector - Eko Eddya Supriyanto; Diryo Suparto; Meida Rachmawati; Jumadil Saputra (CV. Austronesia Akademika, 2024)
The goal of the study is to develop an integrated support model for small and medium-sized tourist firms that involves multi-stakeholder engagement. Specifically, this research identifies the mentoring model needed by SMEs in the tourism sector in Guci Hot Spring Tourism and Tegal Regency and navigates mentoring strategies that suit their needs by including multi-stakeholders. This research uses a qualitative approach with a case study of SMEs in the tourist area of Guci Hot Springs, Tegal Regency. Focus groups and in-depth interviews with SMEs in the tourist industry were employed for the purpose of gathering data. We analyzed 20 informants representing the SME sector in Guci Hot Springs consisting of fashion, culinary, and craft SMEs. Based on the qualitative data analysis carried out, the results state that the integrated assistance model covers substantive points such as marketing development, business permits and SME business entities, social media and information technology, and financial management. For more effective assistance, stakeholder involvement is very necessary. This study shows that stakeholders need their role and capacity to coordinate knowledge, management, and entrepreneurial spirit among SMEs in the tourism sector. As a result, this study's findings advance knowledge of how SMEs in the tourist industry may engage many stakeholders by using an integrated mentoring strategy.